Low-Dose vs. High-Dose Cisplatin: Lessons Learned From 59 Chemoradiotherapy Trials in Head and Neck Cancer - Szturz, Petr; Wouters, Kristien; Kiyota, Naomi; Tahara, Makoto; Prabhash, Kumar; Noronha, Vanita; Adelstein, David; Van Gestel, Dirk; Vermorken, Jan B. (Frontiers in Oncology, 2019)
In locally advanced squamous cell carcinomas of the head and neck (LA-SCCHN), concurrent chemoradiotherapy is an integral part of multimodality management both in the adjuvant and in the definitive settings. Although de-intensification strategies have been propelled to the forefront of clinical research in human papillomavirus (HPV) positive oropharyngeal cancer, three cycles of 100 mg/m2 cisplatin given every three weeks concurrently with conventionally fractionated external beam radiotherapy represent a cost-effective and globally accessible treatment option for the majority of LA-SCCHN cases. Based on four large randomized trials, this regimen has become the non-surgical standard of care for cisplatin-eligible patients. Nevertheless, the outcomes in terms of efficacy, toxicity, and compliance have been rather disappointing. Therefore there is an unmet need to find a better alternative. With limited support from randomized trials, weekly low-dose cisplatin regimens have replaced the standard high-dose schedule at some institutions. Four prospective trials exploring radiotherapy with and without weekly low-dose cisplatin have been published. Two of them were conducted in the 1980s, one of which had a negative outcome, the third study provided insufficient information on toxicity, and the fourth trial had to be prematurely terminated due to poor accrual. Moreover, findings of two phase III trials comparing the two concurrent cisplatin regimens favoured the high-dose protocol. We performed a composite meta-analysis of 59 prospective trials enrolling a total of 5,582 patients. The primary endpoint was overall survival. Reflecting different radiotherapy fractionation schemes and treatment intents, three meta-analyses were carried out, one for postoperative conventional chemoradiotherapy, one for definitive conventional chemoradiotherapy, and one for definitive altered fractionation chemoradiotherapy. In the former two settings, both high- and low-dose regimens yielded similar survival outcomes, thus, the primary objective was not met. When given concurrently with altered fractionation radiotherapy, patients treated with high-dose cisplatin had significantly longer overall survival than those who received low-dose cisplatin. In this article we provide a synthetic view of the results, discuss the issue of cumulative dose, compare two versus three cycles of high-dose cisplatin, and present our three-step recommendations for use of the current standard, high-dose cisplatin, in clinical practice.